2019
DOI: 10.1021/acsenergylett.9b01550
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Calcium Plating and Stripping at Room Temperature Using a Borate Salt

Abstract: Interest has rekindled in reversible calcium plating and stripping, renewing hopes for the development of Ca-ion batteries. However, the development of an electrolyte that operates at room temperature and is stable to oxidation at practical potentials remains a significant barrier. Here we report the synthesis and crystal structure of a new fluorinated alkoxyborate Ca(B(Ohfip) 4 ) 2 •4DME salt. Reversible plating and the dissolution of calcium from pure solutions of this salt in dimethoxyethane are demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
245
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(270 citation statements)
references
References 30 publications
21
245
1
3
Order By: Relevance
“…Taking the consumption of oxygen and the electrons flowing into the reduction of DBBQ into account, one can calculate the expected ratio between transferred electrons per oxygen molecule on the basis of the postulated reactions. This results in 2 e -/O2 for reactions (4) and (5) and 1 e -/O2 for reaction (6). For reaction (6) a following disproportionation reaction of the superoxide is plausible as we also showed in the beginning of this paper (see Figure 5).…”
Section: The Orr Mediation By Dbbq In Ca 2+ Containing Dmsosupporting
confidence: 72%
See 2 more Smart Citations
“…Taking the consumption of oxygen and the electrons flowing into the reduction of DBBQ into account, one can calculate the expected ratio between transferred electrons per oxygen molecule on the basis of the postulated reactions. This results in 2 e -/O2 for reactions (4) and (5) and 1 e -/O2 for reaction (6). For reaction (6) a following disproportionation reaction of the superoxide is plausible as we also showed in the beginning of this paper (see Figure 5).…”
Section: The Orr Mediation By Dbbq In Ca 2+ Containing Dmsosupporting
confidence: 72%
“…Another problem for lithium technology is the lack of the resource lithium and the water consuming mining (3). Thefore Calcium, being the fifth most abundant metal on earth, combines a high abundance with a competitive volumetric capacity of 2072 mAh⋅cm -3 (4,5) and thus, is a promising candidate as anode material in future battery applications. Early studies, however, showed the difficulties of Ca plating/stripping (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdruck mit Genehmigung aus Lit. . Copyright Royal Chemical Society und American Chemical Society (2019).…”
Section: Methodsunclassified
“…1,2 Advances in the development of such batteries are intricate due to the lack of competitive cathode materials and electrolytes. 3,4 While recent findings demonstrate the feasibility of Ca anode operation using different electrolytes, [5][6][7][8] the identification of suitable cathode materials has been facing several roadblocks. 4,9,10 Limited reversible electrochemical Ca intercalation has been reported for a handful of compounds 4 (V 2 O 5 , 11 TiS 2 , 12 MoO 3 , 13 Ca 0.5 CoO 2 , 14 and manganese hexacyanoferrate 1 ), all of them showing poor cycling, if any.…”
Section: Introductionmentioning
confidence: 99%